Thermal behaviour of a gypsum board incorporated with phase change materials - Zhou, Hongxia; Puttige, Anjan Rao; Nair, Gireesh; Olofsson, Thomas (Journal of Building Engineering, 2024)
This study investigates the influence of a microencapsulated Phase Change Material (mPCM) on building systems in a subarctic climate which is not commonly studied for PCM applications. The mPCM is incorporated into gypsum to make a composite board with a volume fraction of 30 vt%. The fabricated composite board is then used to make a box model. This model along with a reference model built only with gypsum boards are placed inside a climate chamber where temperature is regulated to a summer day of a subarctic country, where large temperature variation exists between day and night. In addition, a Finite Element Method (FEM), is also used for the validation of the experimental data. The thermal-physical properties of the mPCM gypsum board including the specific heat capacity and thermal conductivity are measured. The microscopic features of the composite board are also studied. In addition, the temperature variation and the thermal energy storage of the boards of the two models have been studied. Results indicate that incorporation of mPCM into gypsum will change the thermal properties of the material. PCM can work as an additional insulation layer due to its low thermal conductivity. Further, the temperature fluctuation inside of the model with mPCM is reduced. In addition, the energy stored in the mPCM composite is around 3 times higher than that of gypsum board, making it promising for building energy improvement and load shifting.